Cationic pTyr/pSer imprinted polymers based on a bis-imidazolium host monomer: phosphopeptide recognition in aqueous buffers demonstrated by μ-liquid chromatography and monolithic columns. Issue 5 (13th January 2017) - Wierzbicka, Celina; Liu, Mingquan; Bauer, David; Irgum, Knut; Sellergren, Börje
Abstract : Capillary monoliths featuring grafted molecularly imprinted polymer films incorporating on a bis-imidazolium host monomer, displayed a remarkable crossreactivity with phosphorylated peptides in buffered media. Abstract : We report on the design and characterization of imprinted cationic host polymers for selective trapping of phosphoserine and phosphotyrosine peptides. A series of imidazolium host monomers were synthesized and characterized with respect to binding affinity and stoichiometry of interaction with salts of phenylphosphonic acid. The strongest binders were subsequently used for the preparation of imprinted polymers in the form of crushed monoliths, using Fmoc-phosphotyrosine-ethyl ester or Fmoc-phosphoserine-ethyl ester as templates in combination with a hydrophilic crosslinking monomer. The polymers were compared with respect to binding and its dependence on solvent, and whether charged or uncharged host monomers were used. The recipes were subsequently implemented in the capillary monolith format for evaluation by micro-liquid chromatography in both buffered and organic media. Results from both tested formats reveal that the cationic host polymers displayed enhanced recognition in polar and buffered media, in contrast to neutral urea-based hosts which showed best results in acetonitrile rich mobile phases.